Phase IB study of osimertinib in combination with navitoclax in EGFR-mutant NSCLC following resistance to initial EGFR therapy (ETCTN 9903) - Bertino, Erin M. (Clin Cancer Res, 2020)
INTRODUCTION: Osimertinib is an effective therapy in EGFR mutant NSCLC, but resistance invariably develops. Navitoclax is an oral inhibitor of BCL-2/BCL-xL that has exhibited synergy with osimertinib in preclinical models of EGFR-mutant NSCLC. In hematologic malignancies, BCL-2 family inhibitors in combination therapy effectively increase cellular apoptosis and decrease drug resistance. METHODS: This single arm phase IB study evaluated safety, tolerability and feasibility of osimertinib and navitoclax, including dose expansion in T790M+ patients at the recommended phase 2 dose (RP2D). Eligible pts had advanced EGFR-mutant NSCLC with prior TKI exposure. Five dose levels (DL) were planned with osimertinib from 40 – 80 mg PO daily and navitoclax from 150 – 325 mg PO daily. RESULTS: A total of 27 pts were enrolled (18 dose escalation, 9 expansion): median age 65, 67% female, 48% exon 19 del and 37% L858R, median 1 prior line of therapy. The most common adverse events were lymphopenia (37%), fatigue (22%), nausea (22%), and thrombocytopenia (37%). No DLTs were seen in dose escalation; osimertinib 80 mg, navitoclax 150 mg was chosen as the RP2D. Most patients (78%) received >95% of planned doses through 3 cycles. In expansion cohort, objective response rate (ORR) was 100% and median progression-free survival (PFS) was 16.8 months. A pro-apoptotic effect from navitoclax was demonstrated by early-onset thrombocytopenia. CONCLUSIONS: Oral combination therapy with navitoclax and osimertinib was safe and feasible at RP2D with clinical efficacy. Early thrombocytopenia was common, supporting an target engagement by navitoclax. Further study of BCL-2/BCL-xL inhibition to enhance osimertinib activity is warranted.